Horrible harry and the goog eaudiobook - Kline, Suzy (Horrible Harry, 2005)
Early readers will love this great addition to the fun-loving Horrible Harry series from award-winning author Suzy Kline. One day Harry's horrible cat, The Goog, follows Harry's grandmother to school. Now Harry and his friend Doug have to catch The Goog before the old cat gets into too much trouble!